سۆفیگەری و عیرفان لە شیعرەکانی سالمدا - شوانی, پ.د. ئیبراهیم ئەحمەد; عزالدین, م. سۆران بهاءالدین (Sulaimani Journal for Humanities, 2023)
This study is titled: "Sufism and Piety in the Poems of Salim". It is an attempt to reveal the Sufism and piety aspects in Salim's poetry (1805-1869), Theosophy has entered the poetry of Salim in a way and rooted in it in an intentionally and unintentionally Sufi manner, the terms and thoughts of Sufi are reflected in his poems. Once he talks about the Sheikh of Tariqat and once he is melted like a Sufi in the love of mystery lover (Yar), once he calls for the king of Naqshband and once he proudly tells the poetry of Mawlana Khalid Naqshbandi, once he takes the AL-Haliaj way and will disappear in love, another time he wants to correct the wrong path of ascetic and Sufi, and once as a sufi he will be over-sentimental and elating in the love of Yar. This dominant literature reflects the Sufism and Peity literature of his time, and this study reveals this influence on Salim’s poetry.
Keywords: Sufism in poetry; piety; AlHallaj; oversentimental; Salims worldview